NUTRI-ONCOCARE: New integral nutrition care model to prevent and treat malnutrition in cancer patients - Mariola Sirvent-Ochando; Ana Murcia-Lopez; Cristina Sangrador-Pelluz; Sara Espla; Margarita Garrido-Siles; Jimena Abiles (Farmacia Hospitalaria)
Objective: The maximum expression of malnutrition in cancer patients is cancerous cachexia, always linked to an unfavorable prognosis. Given its evolutionary nature it is recommended to detect and act early in those patients with nutritional risk. The objective is to propose an action algorithm for the nutritional approach of patients with solid tumors. Method: Through the nominal group technique, specialists in hospital pharmacy, nutrition and oncology who established a prioritization of issues related to nutritional status and its approach in patients with solid tumors were brought together. Their discussion and analysis allowed us to design a performance algorithm. Results: The algorithm differentiates two groups of patients according to the location of the tumor and its impact on nutritional status: high-risk tumors (group 1) include cancers of the head and neck, upper digestive tract and colorectal and low-risk tumors (group 2) include the rest of the neoplasms. Group 1 patients (with the exception of those with colorectal cancer) are directly assessed nutritionally in the first 3-5 days after their presentation in the Tumor Committee, starting the nutritional support required at that time. Patients in group 2 and those diagnosed with colorectal cancer are screened (through NUTRISCORE) after their presentation in the Committee, those with positive risk being referred to nutritional consultation to perform a complete evaluation and propose treatment options. Patients without nutritional risk are periodically re- evaluated. Follow-up is planned according to cancer therapy, with continuous monitoring in each treatment cycle or during the perioperative period. Conclusions: From the nominal group technique, agreements were reached to propose an algorithm of nutritional approach of the cancer patient. The adoption of the proposed algorithm could reduce variability in institutional clinical practice, promoting a timely and adequate nutritional approach in cancer patients.